Chitin Oligosaccharide N,N0 -Diacetylchitobiose (GlcNAc2) as Antimicrobial Coating against Listeria monocytogenes on Ready-to-Eat Shrimp - Zainal Abidin, Munira; Konstantina Kourmentza, Konstantina Kourmentza; Keshavan Niranjan, Keshavan Niranjan (Mdpi, 2023)
N,N0 -diacetylchitobiose, also known as GlcNAc2 , is a chitin oligosaccharide and is reported to possess antimicrobial activity against pathogenic bacteria. In this study, 1% (w/v) GlcNAc2 solution was applied on ready-to-eat (RTE) shrimp and evaluated as an antimicrobial coating against Listeria monocytogenes during storage at 4 ◦C for 16 days. Texture properties, colour, TBARS values, moisture content and bacterial counts were monitored and analysed every four days. The results indicated that the GlcNAc2 coating retarded the changes in texture properties, TBARS values and moisture content of the RTE shrimp during storage. The presence of GlcNAc2 showed no significant changes in RTE shrimp colour in contrast to the control. However, the growth of L. monocytogenes inoculated on the GlcNAc2 -coated RTE shrimp was slower than that of the control sample with the highest log reduction of 0.5 log CFU/mL being observed. This study showed that the GlcNAc2 used as an antimicrobial coating was able to inhibit the growth of L. monocytogenes, while maintaining the quality of the RTE shrimp during refrigerated storage.